Gambaran Pengetahuan Siswi SMA Negeri I Halong Kabupaten Balangan Tentang Pernikahan Dini - Hakimah, Arymurti Kurnia; Ningrum, Novalia Widiya; Hasanah, Siti Noor (Jurnal Rumpun Ilmu Kesehatan, 2024)
According to UNICEF, early marriage is marriage performed on adolescents who are less than 18 years old. Marriages that take place under the age of 18 contravene the rights to education, pleasure, health and freedom of expression. Low knowledge of adolescents about early marriage is a problem for adolescents in the incidence of early marriage. Data from the National Socioeconomic Survey (SUSENAS) in 2020 recorded that 1 in 9 women aged 20-24 years married while still a child and South Kalimantan was ranked first in Indonesia. The purpose of the study was to find out the picture of knowledge of students of SMA Negeri I Halong, Balangan Regency about Early Marriage. The research method used a descriptive survey, with the sampling used was a total sampling of 48 class X and XI students. The results of the study of students of SMA Negeri I Halong who had good knowledge about early marriage were 16 people (33.33%), enough knowledge 26 people (54.16%) and less than 6 people (12.5%). The conclusion of this study is an overview of the level of knowledge of female students of SMA Negeri I Halong about early marriage respondents from 48 moderately knowledgeable.